Student Opinion of Library Instruction (SOLI) Reports, 2013-2015, 2018-2019 - Valdosta State University, Odum Library (Valdosta State University, 2020)
Odum Library (Valdosta State University). Student Opinion of Library Instruction (SOLI) Reports, 2013-2015, 2018-2019. Valdosta State University. Valdosta, Georgia. Library Annual Reports and Self Studies (UA-15-16-1), Valdosta State University Archives and Special Collections.
1 electronic record, 5 files combined into PDF, 140 pages, 540619 bytes.
Keywords: Annual reports; Valdosta State University. Odum Library; Valdosta State University; Libraries--User satisfaction; Library statistics; Library surveys; Academic libraries--Evaluation